2014
DOI: 10.1097/scs.0000000000000908
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Accuracy of Linear Measurements on Lateral Cephalograms Obtained From Cone-Beam Computed Tomography Scans With Digital Lateral Cephalometric Radiography

Abstract: The results showed that the values obtained in CBCT imaging compared with calculated values of the digital lateral cephalometry much closer to the actual distance are more accurate indicators of this type of imaging and that CBCT permits oral surgeons to visualize the position and surgical anatomy of the tooth as it will be seen in the operating theater and allows orthodontists to plan directional traction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
2
21
1
4
Order By: Relevance
“…Similar scientific studies were conducted on 6 (Shokri A., Khajeh S., Khavid A. ), 23 (Danielle R. Periago, William C. Scarfe), 10 (Oded Yitschaky, Meir Redlich, Yossi Abed) human turtles, where the authors also confirmed the higher accuracy of the analysis using the 3D method [62,63,65].…”
Section: --supporting
confidence: 68%
“…Similar scientific studies were conducted on 6 (Shokri A., Khajeh S., Khavid A. ), 23 (Danielle R. Periago, William C. Scarfe), 10 (Oded Yitschaky, Meir Redlich, Yossi Abed) human turtles, where the authors also confirmed the higher accuracy of the analysis using the 3D method [62,63,65].…”
Section: --supporting
confidence: 68%
“…Shokri et al [40] also performed a similar study with 2D and 3D generated cephalograms and concluded that several landmark measurements were different, in particular the Pog-Go.…”
Section: Intra-observer Reproducibilitymentioning
confidence: 94%
“…For instance, an objective measure of bone-stress-threshold can help predict animals which are prone to skeletal injuries and may also help the surgeons select the right surgical materials to provide optimal mechanical support in correcting bone defects. 4,[20][21][22] In this study we evaluated two such objective measures of bone-stress-threshold i.e., AMR and HLR values. By normalising the bone density to its area, the AMR provides a measure of bone density that is independent of the age, sex or breed of the animal.…”
Section: Discussionmentioning
confidence: 99%